Intraoperative dexmedetomidine infusion is associated with reduced emergence agitation and improved recovery profiles after lung surgery: a retrospective cohort study - Kang X; Tang X; Yu Y; Bao F; Gan S; Zheng W; Zhang J; Zhu S (Dove Medical Press, 2019)
Xianhui Kang,1,* Xiaodong Tang,1,* Yang Yu,1 Fangping Bao,1 Shuyuan Gan,1 Wei Zheng,1 Jian Zhang,2 Shengmei Zhu1 1Department of Anesthesiology, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, China; 2Department of Anesthesiology, The Third People’s Hospital of Chengdu, Chengdu, Sichuan, China *These authors contributed equally to this work Purpose: This retrospective cohort study aimed to investigate the association between intraoperative dexmedetomidine infusion and emergence agitation (EA), and recovery profiles after lung surgery in adult patients. It was hypothesized that dexmedetomidine was associated with reduced EA and improved recovery profiles. Patients and methods: A single-center chart review was conducted on elective lung surgeries in adults between January and December 2016. The primary outcome was the incidence of EA in postanesthesia care units (PACUs). The secondary outcomes included rescue analgesia, shivering, time to extubation, residual sedation, postoperative pulmonary events, duration of PACU stay, length of hospital stay, and intraoperative hemodynamic changes. Univariate and multivariate regression analyses were used to analyze data. Results: Among 2,468 patients, 814 received an intraoperative dexmedetomidine infusion. Intraoperative dexmedetomidine infusion was associated with a lower incidence of EA (10.9% vs 15.0%; adjusted OR, 0.67; 95% CI, 0.51–0.87; P=0.003), rescue analgesia (7.6% vs 12.2%; adjusted OR, 0.63; 95% CI, 0.47–0.86; P=0.003), shivering (4.2% vs 6.6%; adjusted OR, 0.58; 95% CI, 0.38–0.88; P=0.010), and intraoperative bradycardia (18.6% vs 12.6%; adjusted OR, 1.51; 95% CI, 1.19–1.92; P=0.001). No differences were observed in residual sedation, duration of PACU stay, postoperative pulmonary events, and length of hospital stay between the groups. Conclusion: This retrospective study suggested that intraoperative dexmedetomidine infusion was associated with a lower incidence of EA, rescue analgesia, and shivering in adults after lung surgery. Intraoperative bradycardia was the main side effect. Keywords: dexmedetomidine, emergence agitation, intraoperative administration, lung surgery, recovery profiles